Melanoma Inhibitory Activity (MIA) Is Able to Induce Vitiligo-Like Depigmentation in an in vivo Mouse Model by Direct Injection in the Tail - Bordignon, Matteo; Luisetto, Roberto; Valente, Maria Luisa; Fedrigo, Marny; Castellani, Chiara; Angelini, Annalisa; Alaibac, Mauro (Frontiers in Medicine, 2020)
In the complex pathogenesis of vitiligo, the exact mechanism of the dermatosis is still to be clarified. We previously demonstrated that a protein called melanoma inhibitory activity (MIA) is present in non-segmental vitiligo skin and seems to cause the detachment of melanocytes, consequently creating the depigmented macules. In this study, we present an animal model of vitiligo on the basis of the ability of the MIA protein to induce vitiligo-like lesions. Twenty pigmented mice were chosen for the experiments and received injections in the tail with saline (control group) or with saline + MIA protein (treated group). The control group did not show any sign of depigmentation. The treated group showed, instead, clear zones of complete depigmentation in the injected areas in each mouse, with the appearance of white patches with whitening of the hair and a clear-cut edge. Histological examination of the tail in the treated zone showed the absence of melanocytes, without the presence of any inflammatory cell or any sign of skin inflammation patterns, confirming the detachment of the melanocyte operated by the MIA protein. These data seem to confirm a possible role played by the MIA protein in the pathogenesis of vitiligo and may support the development of treatments able to inhibit its action as an alternative therapeutic strategy for this disorder.